Molecular characterization of shrimp harbinger transposase derived 1 (HARBI1)-like and its role in white spot syndrome virus and Vibrio alginolyticus infection. Issue 78 (July 2018) - Sun, Baozhen; Qian, Xiyi; Zhu, Fei
Abstract: The role of the nuclease, HARBI1-like protein (mjHARBI1-like) in the innate immunity of Marsupenaeus japonicus was explored in this study. The 1361 bp cDNA sequence of mjHARBI1-like was cloned from M. japonicus using RACE. RT-qPCR analysis results showed that the gills and hepatopancreas of M. japonicus were the main tissues where mjHARBI1-like is expressed. In addition, it was also found that white spot syndrome virus (WSSV) or Vibrio alginolyticus challenge could stimulate mjHARBI1-like expression. After mjHARBI1-likewas inhibited, expression of immune genes such as toll, p53, myosin, and proPO were significantly downregulated ( P  < 0.01). However, in shrimp hemocytes, hemocyanin and tumor necrosis factor-α (TNF-α) were up-regulated significantly ( P  < 0.01). This study demonstrated that mjHARBI1-like plays a key role in the progression of WSSV and V. alginolyticus infection. Specifically, the cumulative mortality of WSSV-infected and V. alginolyticus -infected shrimp was significantly advanced by double-strand RNA interference (dsRNAi) of mjHARBI1-like. Apoptosis studies indicated that mjHARBI1-dsRNA treatment caused a reduction in hemocyte apoptosis in bacterial and viral groups. In addition, phagocytosis experiments illustrated that mjHARBI1-dsRNA treatment led to a lower phagocytosis rate in hemocytes of V. alginolyticus -challenged shrimp. It was also found that knockdown of mjHARBI1-like inhibited shrimp phenoloxidase (PO) activity, superoxide dismutase (SOD) activity, and total hemocyte count (THC) after WSSV or V. alginolyticus infection. These data indicate a regulative role of mjHARBI1-likein the immunity of shrimp in response to pathogen infection. Resultantly, it was concluded that mjHARBI1-like might have a positive effect on the anti -WSSV immune response of shrimp by regulating apoptosis, THC, PO activity, and SOD activity. Additionally, mjHARBI1-like might promote anti - V. alginolyticus infection by participating in regulating phagocytosis, apoptosis, SOD activity, PO activity, and THC. Highlights: The 1361 bp cDNA sequence of HARBI1-like was cloned from M. japonicus. The mortality of WSSV-infected and V. alginolyticus -infected shrimp was significantly advanced by RNAi of mjHARBI1-like. The mjHARBI1-dsRNA treatment caused a reduction in hemocyte apoptosis in bacterial and viral groups. The mjHARBI1-dsRNA treatment led to a lower phagocytosis rate in hemocytes of V. alginolyticus -challenged shrimp. The mjHARBI1-dsRNA treatment inhibited PO activity, SOD activity, and THC after WSSV or V. alginolyticus infection.